KARAKTERISTIK MUTU SERBUK PEWARNA BUAH NAGA MERAH (Hylocereus polyhizus) HASIL FOAM MAT DRYING DENGAN VARIASI RASIO DAGING DAN KULIT BUAH - Andi Eko Wiyono; Desiyanti rukmasari; Eka Ruriani; Herlina Herlina (Agroindustrial Technology, University of Trunojoyo Madura, 2023)
Pigment is an important part as an indicator of product quality. Natural pigments can be used because they are relatively safe and have low side effects. One of the plants that contain natural pigments is red dragon fruit because it has a high anthocyanin pigment. In addition, the production of red dragon fruit in Jember Regency in 2019 reached 30.7 tons. The high anthocyanin pigment and productivity of red dragon fruit, so that all parts of red dragon fruit in the form of the ratio of flesh and skin of the fruit can be used as raw materials for making natural dyes. The red dragon fruit coloring powder in this study was made by a microencapsulation process using the foam mat drying. This microencapsulation process can extend the shelf life of the dye powder. The purpose of this study was to determine the effect of variations in the ratio of red dragon fruit flesh and skin to the quality characteristics of the dye powder. Research on the quality characteristics of this dye powder uses the ratio of flesh and skin of red dragon fruit. The results showed that all treatments had a significant effect on the quality characteristics of the dye powder in the form of pH value, color value, total dissolved solids value, water content value, water absorption value, and anthocyanin content value. The quality characteristics of the dye powder with 100% skin treatment have a better value than the other treatments. The quality parameters include: the highest anthocyanin content value of 8.437 mg/ml, the highest color intensity value of 11.17, the lowest pH value of 3.28, the lowest percentage decrease in stability of 69%, and the lowest water content value of 3.46%